Stable Isotope Geochemistry - Hoefs, Jochen (Springer Textbooks in Earth Sciences, Geography and Environment, 2018)
This classic textbook is an introduction to the systematics and the use of stable isotopes in geosciences. It is subdivided into three parts: i) theoretical and experimental principles, ii) fractionation processes of light and heavy elements, iii) the natural variations of geologically important reservoirs. Since the publication of the previous edition advances in multicollector-ICP-mass-spectrometry allow precise measurements of new isotope systems. In this new edition therefore, 42 elements with resolvable natural variations in isotope composition are discussed. New findings from non-traditional isotope systems have been incorporated. Many new references have been added, which enable quick access to recent literature.